2009
DOI: 10.1080/09593330902760631
|View full text |Cite
|
Sign up to set email alerts
|

Microthrix parvicellaandGordona amaraein mesophilic and thermophilic anaerobic digestion systems

Abstract: The scope of the study presented in this paper is to determine the fate of the filamentous bacteria Gordona amarae and Microthrix parvicella in anaerobic digestion operating under mesophilic and thermophilic conditions. In order to detect and quantify foaming bacteria in the anaerobic digesters, a fluorescent in situ hybridization (FISH) method was developed and applied. This paper presents the results of a laboratory-scale study that involved the operation of four lab-scale anaerobic digestion systems operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 15 publications
3
17
1
Order By: Relevance
“…The filamentous organisms attach onto the gas bubbles present in anaerobic digesters and rise to the surface of the liquid creating a foam blanket (Jenkins et al 2003). Fragmented filamentous organisms can more evenly distribute foam-associated compounds throughout the digester, increasing foam (Marneri et al 2009). Correlation analysis on Phase 2 data showed that alkalinity (R 2 =0.737), pH (R 2 =0.381), percent total solids (R 2 =0.731), percent volatile solids (R 2 =0.740), and filament counts (R 2 =0.333) that correlated with the Alka-Seltzer foaming potential results.…”
Section: Phasementioning
confidence: 99%
See 4 more Smart Citations
“…The filamentous organisms attach onto the gas bubbles present in anaerobic digesters and rise to the surface of the liquid creating a foam blanket (Jenkins et al 2003). Fragmented filamentous organisms can more evenly distribute foam-associated compounds throughout the digester, increasing foam (Marneri et al 2009). Correlation analysis on Phase 2 data showed that alkalinity (R 2 =0.737), pH (R 2 =0.381), percent total solids (R 2 =0.731), percent volatile solids (R 2 =0.740), and filament counts (R 2 =0.333) that correlated with the Alka-Seltzer foaming potential results.…”
Section: Phasementioning
confidence: 99%
“…Allowing dual-stage anaerobic digestion to be economical to operate since the majority of the sludge stabilization is performed in the mesophilic stage (Cheunbarn and Pagilla 2000). Marneri et al (2009) investigated the foaming potential of dual-stage anaerobic digesters.…”
Section: Dual-stage Anaerobic Digestionmentioning
confidence: 99%
See 3 more Smart Citations